2019
DOI: 10.1002/brb3.1442
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal antibodies in adult patients with new‐onset seizures: A prospective study

Abstract: ObjectivesImmunotherapy in addition to antiepileptic drugs can improve seizure freedom rates in autoimmune epilepsy, highlighting the importance of early diagnosis. A diagnosis of autoimmune epilepsy can be supported by presence of serum antibodies to neuronal antigens. We asked how often neuronal antibodies are found in the serum of unselected adult patients with new‐onset seizures and whether such testing could improve detection of autoimmune epilepsy.Material and MethodsWe included 44 patients over the age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 13 publications
7
6
0
Order By: Relevance
“…Although the sub-cohort of patients receiving immunosuppression is small and no further detailed analysis was performed, previous studies have shown similar trends that early immunotherapy is the mainstay for treatment of autoimmune epilepsy. 19,20,24,[28][29][30] Consistent with our study, a previous study of 32 patients with focal immune epilepsy with predominant or exclusive seizure presentations showed that 81% reported improvement after immunotherapy, and the median time from seizure onset to immunotherapy was 4 months for responders and 22 months for nonresponders. 31 In addition, most patients have established epilepsy, and the long delay of an average of 14.2 years in our cohort between seizure onset and a comprehensive pre-surgical evaluation including workup for immune etiologies underscores the known barrier of delayed diagnosis and referral of focal DRE patients to a comprehensive pre-surgical evaluation.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Although the sub-cohort of patients receiving immunosuppression is small and no further detailed analysis was performed, previous studies have shown similar trends that early immunotherapy is the mainstay for treatment of autoimmune epilepsy. 19,20,24,[28][29][30] Consistent with our study, a previous study of 32 patients with focal immune epilepsy with predominant or exclusive seizure presentations showed that 81% reported improvement after immunotherapy, and the median time from seizure onset to immunotherapy was 4 months for responders and 22 months for nonresponders. 31 In addition, most patients have established epilepsy, and the long delay of an average of 14.2 years in our cohort between seizure onset and a comprehensive pre-surgical evaluation including workup for immune etiologies underscores the known barrier of delayed diagnosis and referral of focal DRE patients to a comprehensive pre-surgical evaluation.…”
Section: Discussionsupporting
confidence: 90%
“…Early diagnosis and treatment are important for focal DRE with potential immune cause because early initiation of immunotherapy is associated with favorable outcome. 20,23,24,28,29 In our study, five of nine (55.5%) showed favorable or possibly favorable responses, which is similar to what has been reported in patients with suspected autoimmune epilepsy with a 62% response rate. 11 In addition, all of the patients in our study who had improved seizure control received immunotherapy ≤7 months after seizure onset, whereas all the nonresponders received immunotherapy trials 1-10 years after seizure onset (Table 4).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Epilepsy and new onset seizures in elderly patients are an important health issue of the aging population ( 1 , 2 ). Epileptic seizures are a core symptom of autoimmune encephalitis (AE) ( 3 , 4 ), and autoimmune epilepsy has been reported to account for up to 20% of epilepsy of unknown etiology ( 5 ). The prevalence ranges from 6% up to 37% ( 3 , 6 ), with non-paraneoplastic AE being more common than paraneoplastic AE.…”
Section: Introductionmentioning
confidence: 99%